Suppression of heat-shock protein synthesis by short-chain fatty acids and alcohols. - Munks, R.J.L.; Turner, B.M. (Biochimica et Biophysica Acta, 1994)
We have shown that ethanol, propanol and butanol (at 0.5-2%) and salts of butyric and propionic acids (at 8-40 mM) all cause a major reduction in heat-shock protein (hsp) synthesis when present in the growth medium of Drosophila cultured cells (Kc and SL2) subjected to either increased temperature or chemical stressors. Inhibition of normal protein synthesis in unstressed cells was comparatively slight, and the usual suppression of synthesis of non-heat-shock proteins in stressed cells was unaffected. Maximum suppression of hsp synthesis occurred only if inhibitors were added before initiation of the stress response, an observation that eliminates the possibility that these findings are due to non-specific, toxic effects. Suppression was accompanied by severely reduced levels of both hsp70 mRNA and active heat-shock factor (HSF). We conclude that the inhibitors act by suppressing the initiation of transcription of heat-shock genes.